AI-Powered Smart Study Planner: Enhancing Personalized Learning Through Intelligent Scheduling - Gagana Lingshetti,; Sarthak Pawar,; Manish Shinde,; Hamja Sayyed, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
In order to improve individualized learning through intelligent scheduling, this paper presents the creation and assessment of a smart study planner driven by artificial intelligence. By combining user behavior analytics, machine learning algorithms, and educational psychology concepts, the suggested system adjusts to time constraints, academic objectives, and individual learning preferences. The system's ability to enhance academic performance, user satisfaction, and learning efficiency is assessed in this study. The planner's capacity to produce flexible, optimized study plans that surpass conventional planning techniques is demonstrated by experimental results obtained from a varied sample of students.
Keywords: AI in Education; Smart Study Planner; Personalized Learning; Intelligent Scheduling; Machine Learning in Education